2018
DOI: 10.21873/anticanres.12205
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Induces Apoptotic Cell Death Through Caspase- and Mitochondria-dependent Pathways in Human Osteosarcoma U-2 OS Cells

Abstract: Our findings provide important insight into the cytotoxic effects of ouabain on U-2 OS cells, in vitro, which are mediated at least partly via cell apoptosis induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…On the contrary, they conduct the delayed suppression effect on renal cancer and prostate cancer growth via other pathways, including caspase‐3 activation, with migration inhibition. Apoptosis of tumor cells can be induced by the activation of the PARP‐bcl‐2‐caspase 3 pathway, which also is related to mitochondria activity 36, 37, 38. Different urological cancers present different sensitivity and related cytotoxicity by niclosamide and B17 derivative via PARP‐bcl‐2 signal pathway in this study.…”
Section: Discussionmentioning
confidence: 67%
“…On the contrary, they conduct the delayed suppression effect on renal cancer and prostate cancer growth via other pathways, including caspase‐3 activation, with migration inhibition. Apoptosis of tumor cells can be induced by the activation of the PARP‐bcl‐2‐caspase 3 pathway, which also is related to mitochondria activity 36, 37, 38. Different urological cancers present different sensitivity and related cytotoxicity by niclosamide and B17 derivative via PARP‐bcl‐2 signal pathway in this study.…”
Section: Discussionmentioning
confidence: 67%
“…We found that in OSC, blocking Na + /K + -exchanging ATPase with ouabain induced cell death at the later time points (days 7, 10, 14). In a similar study, Chou et al ( 2018 ) investigated the effect of ouabain on apoptotic cell death of human osteosarcoma-derived U-2 OS cells. Based on their finding they suggest that blocking Na + /K + -exchanging ATPase with ouabain induced S-G2/M phase cell-cycle arrest in osteosarcoma cells, which in turn induced apoptotic cell death by activating the caspase-dependent and -independent pathways, accompanied also by mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GAS5 promoted the apoptosis of ovarian cancer cells via caspase-3 and caspase-9 upregulation (37). Additionally, the oncogenesis of some cartilage tumors, including chondrosarcoma and chondroblastic osteosarcoma, has exhibited a high correlation with the mitochondrial pathway of apoptosis (3840). Future studies on these tumors are required to further verify the function of GAS5 in mitochondrial apoptosis, providing that GAS5, as a tumor suppressor, may inhibit tumor growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%